Enterprise Risk Management dan Intellectual Capital Pada Earnings Response Coefficient - Haryanti, Angelia Putri Surya; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 33 No 1 (2023)DO - 10.24843/EJA.2023.v33.i01.p12, 2023)
The background of this research is some of the results of previous research regarding the informativeness of the value of profit (value relevance). The research objective is to find empirical evidence of the influence of enterprise risk management and intellectual capital on the earnings response coefficient. The study uses size and industry type control variables with multiple linear regression data analysis techniques. The research sample is 143 companies with purposive sampling as the sampling method. The results show that enterprise risk management has no effect on the earnings response coefficient, while intellectual capital has a positive effect on the earnings response coefficient. Size and industry type control variables have a positive effect on the earnings response coefficient. Keywords: Enterprise Risk Management; Intellectual Capital; ERC